Manufacturing method for SiC / Si composite material

The method of forming and sintering thin layers of a silicon carbide and novolac-type phenolic resin mixture, followed by silicon impregnation, addresses the complexity and time issues in SiC/Si composite material production, enabling efficient manufacturing of complex shapes with high mechanical properties.

JP7660409B2Active Publication Date: 2025-04-11GUN EI CHEM IND +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021047314
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-22
Publication Date
2025-04-11
Estimated Expiration
2041-03-22

AI Technical Summary

Technical Problem

Existing methods for manufacturing SiC/Si composite materials are complex and time-consuming, especially when producing shapes with high complexity, due to the need for multiple processing steps and the use of assisting agents.

Method used

A method involving the formation of a thin layer of a raw material mixture containing silicon carbide particles and a novolac-type phenolic resin, followed by laser irradiation and sintering to create a sintered thin layer. This process is repeated multiple times to build up a laminated structure, which is then further cured and carbonized before being impregnated with silicon to produce the SiC/Si composite material.

Benefits of technology

This method simplifies the manufacturing process, reduces the number of steps required, and allows for the production of SiC/Si composite materials with complex shapes, while maintaining high strength and Young's modulus properties without the need for assisting agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660409000003
    Figure 0007660409000003
  • Figure 0007660409000001
    Figure 0007660409000001
  • Figure 0007660409000002
    Figure 0007660409000002
Patent Text Reader

Abstract

To provide a manufacturing method of a SiC / Si composite material which can be manufactured by a simplified manufacturing process even when manufacturing a SiC / Si composite material having complex shape.SOLUTION: A manufacturing method of a SiC / Si composite material includes the steps of: (a) forming a resin composition for molding containing a novolak type phenolic resin and a hardener and a thin layer of a raw material mixture containing a silicon carbide particle, followed by sintering the thin layer by laser irradiation for forming a sintered thin layer; (b) obtaining a molding (1) by performing the step (a) plural times; (c) obtaining a molding (2) by hardening the resin composition for molding contained in the molding (1); (d) obtaining a fired body by carbonizing an organic component contained in the molding (2); and (e) obtaining a SiC / Si composite material by impregnating silicon in the fired body, followed by reaction sintering the fired body. A rate of the novolak type phenolic resin to 100 pts.mass of the silicon carbide particles is 10-40 pts.mass, and a gelation time of the resin composition for molding at 150°C is 120 seconds or under.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a SiC / Si composite material. [Background technology]

[0002] SiC / Si (silicon carbide / silicon) composite materials have excellent properties such as being lighter, more rigid, and having less thermal expansion than metallic materials, and are used as components in semiconductor manufacturing equipment and other applications. For example, Patent Document 1 discloses a method for producing a SiC / Si composite material by hot pressing a mixture containing silicon carbide powder and a thermosetting resin to obtain a porous SiC molded body, degreasing the body, and then impregnating the body with silicon.

[0003] The SiC / Si composite material thus obtained is cut into a desired shape as required. However, since SiC / Si composite materials are difficult to process, it is difficult to process them into complex shapes. Therefore, a method has been proposed in which a molded body of the desired shape is produced by an additive manufacturing method using raw materials containing silicon carbide particles and resin components, and the molded body is hardened and carbonized, and then impregnated with silicon. For example, Patent Document 2 discloses a method for producing a reactive sintered silicon carbide component, in which a thin layer of raw material containing silicon carbide particles and nylon is irradiated with a laser to form a sintered thin layer, and a molded body obtained by repeating the process multiple times is impregnated with at least one of a phenol resin and a sugar as an assistant agent for increasing the carbon content, and after sequentially curing and carbonizing, the molded body is impregnated with silicon. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5706076 [Patent Document 2] Patent No. 6651754 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the method described in Patent Document 2 requires a step of impregnating the molded body with an assist agent, which not only takes time for the treatment but also increases the number of steps. An object of the present invention is to provide a method for producing a SiC / Si composite material, which can simplify the production steps even when producing a SiC / Si composite material having a complex shape. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] A step (a) of forming a thin layer of a raw material mixture containing silicon carbide particles and a molding resin composition, irradiating a desired area of ​​the thin layer with a laser, and sintering the thin layer to form a sintered thin layer; A step (b) of performing the step (a) multiple times to obtain a molded body (1) in which multiple sintered thin layers are laminated; A step (c) of further curing the molding resin composition contained in the molded body (1) to obtain a molded body (2); A step (d) of carbonizing the organic components contained in the molded body (2) to obtain a fired body; (e) impregnating the sintered body with silicon and reactively sintering the sintered body to obtain a SiC / Si composite material; Including, The molding resin composition contains a novolac phenolic resin and a curing agent, the ratio of the novolac-type phenolic resin to 100 parts by mass of the silicon carbide particles is 10 to 40 parts by mass; A method for producing a SiC / Si composite material, wherein the gel time of the molding resin composition at 150° C. is 120 seconds or less. [2] The method for producing a SiC / Si composite material according to [1] above, wherein the molding resin composition further contains a curing accelerator. [3] The method for producing a SiC / Si composite material according to [1] or [2] above, wherein the novolac-type phenolic resin has a mass average molecular weight of 2,000 to 20,000. Effect of the Invention

[0007] According to the present invention, it is possible to provide a method for producing a SiC / Si composite material, which can simplify the production steps even when producing a SiC / Si composite material having a complex shape. [Brief description of the drawings]

[0008] [Figure 1] 5A and 5B are diagrams for explaining a method for measuring the amount of deflection, in which FIG. 5A shows the state before heat treatment, and FIG. 5B shows the state after heat treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Manufacturing method of SiC / Si composite material] Hereinafter, one embodiment of the method for producing a SiC / Si composite material of the present invention will be described. The method for producing a SiC / Si composite material of this embodiment includes the following steps (a) to (e). The SiC / Si (silicon carbide / silicon) composite material obtained by the present invention is a metal matrix composite material (MMC = Metal Matrix Composites) consisting of silicon as a metal matrix and silicon carbide as a ceramic reinforcing material.

[0010] <Process (a)> Step (a) is a step of forming a thin layer of a raw material mixture containing silicon carbide particles and a molding resin composition, irradiating a desired region of the thin layer with a laser, and sintering the thin layer to form a sintered thin layer. The molding resin composition is cured by irradiating a desired region of the thin layer with a laser. In this specification, the curing of the molding resin composition in step (a) is also referred to as "primary curing". The raw material mixture used in the step (a) contains silicon carbide particles (SiC) and a molding resin composition.

[0011] (Silicon carbide particles) The average particle size of the silicon carbide particles is preferably 10 to 120 μm, more preferably 30 to 80 μm. If the average particle size of the silicon carbide particles is equal to or greater than the lower limit, the flowability of the raw material mixture is increased, and the recoatability is excellent. If the average particle size of the silicon carbide particles is equal to or less than the upper limit, the thin layer of the raw material mixture can be easily thinned, the laser is sufficiently irradiated to the inside of the thin layer, and the molding resin composition is sufficiently cured. In addition, the smoothness of the surface of the sintered thin layer during laser irradiation is improved. The average particle size of the silicon carbide particles is a particle size (median size) corresponding to a cumulative frequency of 50% on a volume distribution basis of the silicon carbide particles measured by a laser diffraction method.

[0012] The silicon carbide particles may be used alone or in the form of a mixture of two or more types having different average particle sizes in any ratio. The silicon carbide particles may be granulated particles obtained by granulating a plurality of particles. The average particle size of the granulated particles is preferably 10 to 120 μm, and more preferably 30 to 80 μm. The granulated particles can be obtained by using a binder such as nylon, polyethylene, polystyrene, acrylic resin, polyvinyl alcohol, etc., and by a known granulation method such as spray drying, a fluidized bed method, or a rolling method.

[0013] (Molding resin composition) The molding resin composition contains a novolac type phenolic resin and a curing agent. The molding resin composition preferably further contains a curing accelerator. The molding resin composition may further contain components (optional components) other than the novolac type phenolic resin, the curing agent, and the curing accelerator, as necessary.

[0014] <<Novolac type phenolic resin>> Novolac-type phenolic resins are resins obtained by reacting at least one of phenols and bisphenols with aldehydes in the presence of an acid catalyst. Examples of phenols include phenol, o-cresol, m-cresol, p-cresol, 2,3-xylenol, 3,5-xylenol, m-ethylphenol, m-propylphenol, m-butylphenol, p-butylphenol, o-butylphenol, resorcinol, hydroquinone, catechol, 3-methoxyphenol, 4-methoxyphenol, 3-methylcatechol, 4-methylcatechol, methylhydroquinone, 2-methylresorcinol, 2,3-dimethylhydroquinone, 2,5-dimethylresorcinol, 2-ethoxyphenol, 4-ethoxyphenol, 4-ethylresorcinol, 3-ethoxy-4-methoxyphenol, 2-propenylphenol, 2-isopropylphenol, 3-isopropylphenol, 4-isopropylphenol, 3,4,5-trimethylphenol, 2-isopropoxyphenol, 4-propoxyphenol, 2-allyl ...propoxyphenol, 4-propoxyphenol, 2-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-prop trimethoxyphenol, 4-isopropyl-3-methylphenol, pyrogallol, phloroglucinol, 1,2,4-benzenetriol, 5-isopropyl-3-methylphenol, 4-butoxyphenol, 4-t-butylcatechol, t-butylhydroquinone, 4-t-pentylphenol, 2-t-butyl-5-methylphenol, 2-phenylphenol, 3-phenylphenol, 4-phenylphenol, 3-phenoxyphenol, 4-phenoxyphenol, 4-hexyloxyphenol, 4-hexanoylresorcinol, 3,5-diisopropylcatechol, 4-hexylresorcinol, 4-heptyloxyphenol, 3,5-di-t-butylphenol, 3,5-di-t-butylcatechol, 2,5-di-t-butylhydroquinone, di-sec-butylphenol, 4-cumylphenol, nonylphenol, 2-cyclopentylphenol, 4-cyclopentylphenol, and the like. These phenols may be used alone or in combination of two or more. Examples of bisphenols include bisphenol A, bisphenol F, bisphenol C, bisphenol S, bisphenol E, and bisphenol Z. The bisphenols may be used alone or in combination of two or more kinds in any desired ratio.

[0015] Examples of aldehydes include formaldehyde, trioxane, furfural, paraformaldehyde, benzaldehyde, methyl hemiformal, ethyl hemiformal, propyl hemiformal, salicylaldehyde, butyl hemiformal, phenyl hemiformal, acetaldehyde, propyl aldehyde, phenylacetaldehyde, α-phenylpropyl aldehyde, β-phenylpropyl aldehyde, o-hydroxybenzaldehyde, m-hydroxybenzaldehyde, p-hydroxybenzaldehyde, o-chlorobenzaldehyde, o-nitrobenzaldehyde, m-nitrobenzaldehyde, p-nitrobenzaldehyde, o-methylbenzaldehyde, m-methylbenzaldehyde, p-methylbenzaldehyde, p-ethylbenzaldehyde, and pn-butylbenzaldehyde. The aldehydes may be used alone or in a mixture of two or more kinds in any ratio.

[0016] Examples of the acid catalyst include hydrochloric acid, sulfuric acid, phosphoric acid, sulfonic acid, carboxylic acid, and salts with metals such as zinc chloride or zinc acetate. Examples of sulfonic acids include paratoluenesulfonic acid, xylenesulfonic acid, benzenesulfonic acid, and methanesulfonic acid. Examples of the carboxylic acid include lactic acid, citric acid, malic acid, tartaric acid, malonic acid, succinic acid, maleic acid, oxalic acid, acetic acid, and benzoic acid. The acid catalyst may be used alone or in combination of two or more kinds in any desired ratio.

[0017] The reaction of at least one of phenols and bisphenols with aldehydes can be carried out by a known method. For example, a method of charging at least one of phenols and bisphenols, aldehydes, an acid catalyst, water, etc. into a reaction vessel and maintaining an arbitrary reaction temperature for an arbitrary reaction time can be mentioned. After the reaction is completed, the reaction liquid is neutralized as necessary, and the reaction liquid is further concentrated under reduced pressure to remove water, thereby obtaining a novolac type phenolic resin. In addition, a silane coupling agent may be added as necessary before or after neutralization of the reaction liquid. In this case, a mixture containing a novolac type phenolic resin and a silane coupling agent is obtained. Examples of the silane coupling agent include N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane. The silane coupling agent may be used alone or in combination of two or more kinds in any desired ratio.

[0018] The mass average molecular weight of the novolac phenolic resin is preferably 2000 to 20000, more preferably 3000 to 17000, and even more preferably 4000 to 15000. If the mass average molecular weight of the novolac phenolic resin is equal to or greater than the lower limit, the raw material mixture is less likely to block. As will be described in detail later, the molded body (1) obtained in step (b) is taken out by removing the raw material mixture in the region (non-irradiated region) where the thin layer of laser is not irradiated. The less the raw material mixture is blocked, the easier it is to remove the raw material mixture in the non-irradiated region, and the time required to take out the molded body (1) (removal work time) can be shortened, improving the workability of removal. In addition, if the mass average molecular weight of the novolac phenolic resin is equal to or greater than the lower limit, the gelation time of the molding resin composition tends to be shortened. If the mass average molecular weight of the novolac phenolic resin is equal to or less than the upper limit, the novolac phenolic resin can be easily produced. The mass average molecular weight of the novolac phenolic resin is a value measured by gel permeation chromatography (GPC) using polystyrene as a standard substance.

[0019] The average particle size of the novolac phenolic resin is preferably 5 to 100 μm, more preferably 10 to 80 μm. If the average particle size of the novolac phenolic resin is equal to or greater than the lower limit, the flowability of the raw material mixture is increased, and the recoatability is excellent. If the average particle size of the novolac phenolic resin is equal to or less than the upper limit, the thin layer of the raw material mixture can be easily thinned, the laser is sufficiently irradiated to the inside of the thin layer, and the molding resin composition is sufficiently cured. In addition, the smoothness of the surface of the sintered thin layer during laser irradiation is improved. The average particle size of the novolac phenolic resin is a particle size (median size) that corresponds to a cumulative frequency of 50% based on the volume distribution of silicon carbide particles measured by a laser diffraction method.

[0020] The ratio of the novolac-type phenolic resin is 10 to 40 parts by mass relative to 100 parts by mass of silicon carbide particles, preferably more than 10 parts by mass and not more than 40 parts by mass, more preferably more than 10 parts by mass and not more than 30 parts by mass, even more preferably 15 to 30 parts by mass, and particularly preferably 15 to 20 parts by mass. If the ratio of the novolac-type phenolic resin is equal to or more than the lower limit, the amount of carbon contained in the fired body described later becomes sufficient, and the Young's modulus of the SiC / Si composite material increases. In addition, the moldability of the molded body (1) described later is improved. If the ratio of the novolac-type phenolic resin is equal to or less than the upper limit, the surface smoothness of the sintered thin layer during laser irradiation is improved.

[0021] <<Hardening agent>> Examples of the curing agent include hexamethylenetetramine, hexaethylenetetramine, hexamethoxymethylolmelamine, resol-type phenolic resins, etc. Among these, hexaethylenetetramine is preferred from the viewpoints of storage stability and cost. The curing agent may be used alone or in combination of two or more kinds in any desired ratio.

[0022] The ratio of the curing agent is preferably 3 to 25 parts by mass, more preferably 5 to 20 parts by mass, and even more preferably 7 to 18 parts by mass, relative to 100 parts by mass of the novolac phenolic resin. When the ratio of the curing agent is equal to or higher than the lower limit, the novolac phenolic resin is sufficiently cured. When the ratio of the curing agent is equal to or lower than the upper limit, the generation of gas such as ammonia can be reduced.

[0023] <<Curing accelerator>> Examples of the hardening accelerator include benzoic acid, salicylic acid, and resorcinol. The curing accelerator may be used alone or in combination of two or more kinds in any desired ratio.

[0024] The ratio of the curing accelerator is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 4.5 parts by mass, and even more preferably 1.5 to 4.5 parts by mass, relative to 100 parts by mass of the novolac phenolic resin. If the ratio of the curing accelerator is equal to or greater than the lower limit, the curing of the novolac phenolic resin is accelerated, and the gelation time of the molding resin composition is shortened. If the ratio of the curing accelerator is equal to or less than the upper limit, the decrease in strength due to excessive addition can be suppressed.

[0025] <<Optional ingredients>> Optional components include, for example, resol type phenolic resins, flow aids, carbon, boron carbide, silane coupling agents, lubricants, and the like.

[0026] <<Gelation time>> The gelation time of the molding resin composition at 150°C is 120 seconds or less, preferably 100 seconds or less. If the gelation time of the molding resin composition is the above upper limit or less, the molding resin composition is sufficiently cured by laser irradiation. If the molding resin composition is sufficiently cured, the handling strength is increased. Therefore, as will be described later in detail, when the raw material mixture in the non-irradiated region of the thin layer is removed in step (c) to take out the molded body (1) and the molding resin composition is further cured in a thermostatic oven or the like, the molded body (1) is not easily broken, and the molded body (1) can be easily moved to the thermostatic oven or the like. In addition, since the molding resin composition is sufficiently cured, even if the molding resin composition is further cured in step (c), the obtained molded body (2) is less likely to bend or shrink compared to the molded body (1). The gelation time of the molding resin composition is preferably shorter, and although there is no particular lower limit, it is usually 5 seconds or more. That is, the gelation time of the molding resin composition is preferably 5 to 120 seconds, and more preferably 5 to 100 seconds. The gel time of the molding resin composition is a value measured in accordance with the JACT test method RS-5 "Gel Time Test Method."

[0027] (Preparation of raw material mixture) The raw material mixture is obtained by mixing silicon carbide particles and a molding resin composition. Alternatively, the silicon carbide particles may be mixed with the molding resin composition and then granulated. Granulation can be carried out by a known granulation method such as spray drying, fluidized bed method, or rolling method using a binder such as nylon, polyethylene, polystyrene, acrylic resin, or polyvinyl alcohol.

[0028] (Formation of thin sintered layer) The formation of the sintered thin layer will be described later in step (b).

[0029] <Process (b)> Step (b) is a step of performing the step (a) multiple times to obtain a molded body (1) in which multiple sintered thin layers are laminated. The above-mentioned steps (a) and (b) are carried out, for example, by three-dimensional additive manufacturing as follows. As the three-dimensional additive manufacturing, a selective laser sintering method (SLS method) is suitable.

[0030] First, three-dimensional data of the cross-sectional shape of the desired SiC / Si composite material at a fixed interval is created in advance. Based on this three-dimensional data, a thin layer made of a raw material mixture is laminated on the bottom surface of a molding chamber installed in a three-dimensional lamination device such as a powder additive manufacturing machine. A laser is scanned and irradiated to heat the desired area of ​​this thin layer, thereby sintering the thin layer to form a sintered thin layer (step (a)). The bottom of the modeling chamber is a modeling table, which can be moved up and down. After the sintered thin layer is formed, the bottom surface of the building chamber (building table) is lowered by one layer, another thin layer of the raw material mixture is laminated on the sintered thin layer, and the desired area of ​​this thin layer is scanned and irradiated with a laser. These lamination and irradiation operations are repeated until the desired SiC / Si composite material is formed, and a molded body (1) is obtained (step (b)). The molded body (1) obtained in this way is porous. The thickness of one thin layer is preferably 30 to 200 μm, and more preferably 100 to 150 μm.

[0031] It is preferable to use a laser having an irradiation output of at least 10 W. This melts the molding resin composition contained in the raw material mixture, and the raw material mixture is sintered stably. Types of lasers include CO2 lasers, YAG lasers, and semiconductor lasers.

[0032] <Process (c)> Step (c) is a step of further curing the molding resin composition contained in the molded product (1) to obtain a molded product (2). In this specification, the curing of the molding resin composition in step (c) is also referred to as "secondary curing".

[0033] The molded body (1) is shaped while being embedded in the powder of the raw material mixture. Therefore, prior to the secondary curing of the molding resin composition, the raw material mixture in the area (non-irradiated area) not irradiated with the thin layer of laser, i.e., the raw material mixture where the molding resin composition has not been primarily cured, is removed with a brush, vacuum cleaner, or the like to take out the molded body (1). The removed molded body (1) is then moved, for example, to a thermostatic oven or the like and heat-treated to secondary cure the molding resin composition.

[0034] The curing temperature and curing time of the secondary curing may be appropriately adjusted in consideration of the size, shape, etc. of the molded body (2) to be obtained. Usually, the curing temperature is about 150 to 300° C., and preferably 170 to 250° C., and the curing time is about 1 to 60 minutes, and preferably 1 to 30 minutes. The secondary curing may be carried out under normal pressure or under pressure.

[0035] <Process (d)> Step (d) is a step of carbonizing the organic components contained in the molded body (2) to obtain a fired body. The organic components contained in the molded body (2) are organic compounds in the molding resin composition contained in the raw material mixture, specifically, novolac type phenolic resin, hardener, hardening accelerator, and the like. The carbonization treatment for carbonizing the molded body (2) may be carried out under normal pressure or under reduced pressure (vacuum). The carbonization treatment may be carried out under an oxidizing atmosphere or an inert atmosphere. In particular, the carbonization treatment is preferably carried out under reduced pressure and an inert atmosphere. Here, the "oxidizing atmosphere" refers to an air atmosphere or an atmosphere containing a known oxidizing substance such as oxygen. To provide an inert atmosphere, an inert gas such as helium, argon, or nitrogen may be used.

[0036] The carbonization temperature and time of the carbonization treatment may be appropriately adjusted in consideration of the type of novolac-type phenolic resin contained in the raw material mixture, the size and shape of the fired body to be obtained, etc. In general, the carbonization temperature is preferably 300 to 1200° C., and the carbonization time is preferably 10 to 25 hours.

[0037] <Process (e)> Step (e) is a step of impregnating the sintered body with silicon and reactively sintering the sintered body to obtain a SiC / Si composite material. Since the molded body (1), the molded body (2) and the sintered body are all porous, the voids in the sintered body are filled with silicon by impregnating the sintered body with silicon.

[0038] The SiC / Si composite material can be obtained, for example, by heating a sintered body and silicon to a temperature equal to or higher than the melting temperature of silicon, impregnating the sintered body with the molten silicon, and simultaneously causing reactive sintering. The impregnation temperature is not particularly limited as long as it is equal to or higher than the melting temperature of silicon, but is usually preferably 1450 to 1750° C. The impregnation time is preferably 2 to 25 hours. The impregnation of the fired body with silicon may be carried out under normal pressure or under reduced pressure, but is preferably carried out under reduced pressure from the viewpoint of facilitating the impregnation of silicon.

[0039] By impregnating the sintered body with silicon and reactive sintering it, the silicon impregnated in the sintered body reacts with the carbon contained in the sintered body before being impregnated with silicon, producing silicon carbide. The amount of silicon to be impregnated into the sintered body (impregnation amount) is preferably larger than the amount of silicon calculated by calculating the amount of silicon to react with carbon and the amount of silicon to be filled in the voids of the sintered body from the density of the sintered body and the amount of carbon contained in the sintered body. Specifically, the impregnation amount of silicon is preferably 1.2 to 1.5 times the calculated amount of silicon. By impregnating the sintered body with excess silicon, a large amount of silicon carbide can be produced, and a SiC / Si composite material with a high proportion of silicon carbide, i.e., high density and excellent ceramic properties can be obtained.

[0040] <Action and effect> According to the manufacturing method of the SiC / Si composite material of this embodiment described above, a raw material mixture containing 10 to 40 parts by mass of novolac-type phenolic resin relative to silicon carbide particles is used, and a molded body (1) in which the molding resin composition is primarily cured is molded by three-dimensional additive manufacturing. Therefore, the amount of carbon contained in the fired body is sufficient, and a SiC / Si composite material with sufficient strength and Young's modulus can be obtained even without impregnating the molded body (1) with an assisting agent containing a carbon source. Therefore, in the manufacturing method of the SiC / Si composite material of this embodiment, a process of impregnating the molded body (1) with an assisting agent is not required, and the manufacturing process can be simplified to manufacture the SiC / Si composite material with good productivity. In addition, since the molded body (1) is molded by three-dimensional additive manufacturing, even SiC / Si composite materials with complex shapes can be easily manufactured. Here, the "assist agent" refers to a component that increases the amount of carbon contained in the fired body and enhances the strength of the fired body. Examples of the assist agent include thermosetting resins such as phenolic resins (e.g., resol-type phenolic resins, novolac-type phenolic resins, etc.), melamine resins, unsaturated polyester resins, epoxy resins, polyurethane resins, polyimide resins, and urea resins; and sugars such as monosaccharides (e.g., α-glucose), disaccharides (e.g., maltose, sucrose, etc.), oligosaccharides, and polysaccharides.

[0041] In addition, since the gelation time of the molding resin composition is 120 seconds or less, the molding resin composition is sufficiently cured by primary curing, and a molded body (1) having high handling strength can be obtained. Therefore, when removing the raw material mixture in the non-irradiated region of the thin layer to take out the molded body (1), the molded body (1) is not easily broken and can be easily moved. Furthermore, since the molding resin composition is sufficiently cured by primary curing in the molded body (1), even if the molded body (1) is subjected to a secondary curing treatment, the molded body (2) is less likely to warp or shrink compared to the molded body (1).

[0042] <Application> The SiC / Si composite material obtained by the present invention is suitable for use in components that require light weight and high rigidity, such as semiconductor manufacturing equipment, liquid crystal manufacturing equipment, furnace materials, heat dissipation components, and heat sinks. EXAMPLES

[0043] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. The materials used in each example are shown below. Various measurement methods are also shown below.

[0044] [Materials used] The novolac type phenolic resin used was as follows: Novolac-type phenolic resin (i): Trade name "Resitop PSM-4261" manufactured by Gun-ei Chemical Industry Co., Ltd., mass average molecular weight 1050. Novolac-type phenolic resin (ii): Trade name "Resitop PS-1002" manufactured by Gun-ei Chemical Industry Co., Ltd., mass average molecular weight 4160. Novolac-type phenolic resin (iii): Trade name "Resitop PS-1299" manufactured by Gun-ei Chemical Industry Co., Ltd., weight average molecular weight 13,570. The mass average molecular weight of the novolac phenolic resin was measured using a GPC measuring device (HLC8320GPC, manufactured by Tosoh Corporation) and a column (TSKgel G3000HXL+G2000HXL+G2000HXL, manufactured by Tosoh Corporation) with polystyrene as a standard substance.

[0045] As the silicon carbide particles, SiC powder (particle size #320, average particle diameter 50 μm) manufactured by ESK-SiC Corporation was used. As the curing agent, hexaethylenetetramine (manufactured by Mitsubishi Gas Chemical Company, Inc.) was used. As the curing accelerator, at least one of benzoic acid (manufactured by EMERALD KALAMA CHEMICAL) and resorcinol (manufactured by Sumitomo Chemical Co., Ltd.) was used.

[0046] [Measurement method] <Gelation time measurement> The gel time of the molding resin composition was measured in accordance with JACT test method RS-5 "Gel Time Test Method".

[0047] <Measurement of reaction rate> The reaction rate of the molded body (1) was calculated as follows based on the measured values ​​of the raw material mixture and the molded body (1) by differential scanning calorimetry (DSC). The areas of the regions defined by the DSC curves of the raw material mixture and the molded body (1) represent the heat values ​​of the molding resin compositions contained in the raw material mixture and the molded body (1), respectively, and the area values ​​become smaller as curing progresses. In this specification, the areas of the regions defined by the DSC curves of the raw material mixture and the molded body (1) are defined as the "DSC peak areas" of each. The DSC peak area of ​​the raw material mixture was measured using a differential scanning calorimeter (manufactured by Hitachi High-Tech Science Corporation, product name "DSC6220"). Similarly, the DSC peak area of ​​the molded body (1) was measured. The molded body (1) had been pulverized in advance. The reaction rate was calculated using the following formula. Reaction rate (%) = {(DSC peak area of ​​raw material mixture) - (DSC peak area of ​​molded body (1))} / (DSC peak area of ​​raw material mixture) x 100

[0048] <Measurement of removal work time> After step (b), the time required to remove the raw material mixture from the non-irradiated area of ​​the thin layer and to remove the molded body (1) was measured and defined as the removal operation time.

[0049] <Measurement of bending strength> The bending strength of the molded body (1) was measured using a digital molding sand strength tester (manufactured by Takachiho Seiki Co., Ltd.) in accordance with the measurement method described in JACT test method SM-1.

[0050] <Measurement of deflection amount> As shown in Fig. 1(a), two pedestals 10 were placed 30 mm apart in a constant temperature incubator with airflow (manufactured by Yamato Scientific Co., Ltd., product name "DKN402"). The pedestals 10 were rectangular columns measuring 15 mm in length, 15 mm in width, and 20 mm in height. The molded body (1) 20 was placed on the horizontal surfaces 10a of the two pedestals 10 so that the longitudinal center of the molded body (1) was located halfway between the two pedestals 10, and was heat-treated (secondary curing) at 120° C. for 30 minutes. As shown in Fig. 1(b), the more insufficient the primary hardening is, the more the molded body (2) 30 obtained by the secondary hardening is in a state of being bent downward. The amount of displacement of the bend, that is, the distance r from the extension line of the horizontal plane 10a of the two pedestals 10 to the most bent part of the molded body (2) 30, was taken as the amount of bend.

[0051] <Measurement of secondary hardening shrinkage rate> The total length (L1) in the longitudinal direction of the molded body (1) and the total length (L2) in the longitudinal direction of the molded body (2) were each measured with a digital caliper (manufactured by Mitutoyo Corporation, product name "CD-S20CT"), and the secondary hardening shrinkage rate was calculated from the following formula. Secondary hardening shrinkage rate (%) = (L1 - L2) / L1 × 100

[0052] <Measurement of Young's modulus> The Young's modulus of the SiC / Si composite material was determined by the resonance method in accordance with ISS R 1602.

[0053] [Example 1] <Preparation of raw material mixture> 20 parts by mass of novolak-type phenolic resin (ii) and 1.6 parts by mass of hexaethylene tetramine were pulverized with a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdery resin composition for molding. The average particle diameter of the novolak-type phenolic resin (ii) in the resin composition for molding was 22 μm. The gelation time of the obtained resin composition for molding was measured. The results are shown in Table 1. The total amount (21.6 parts by mass) of the resin composition for molding and 100 parts by mass of SiC powder were mixed with a screw-type mixer for 5 minutes to obtain a raw material mixture.

[0054] <Manufacture of SiC / Si composite material> Using a powder bed fusion machine (manufactured by EOS, product name "EOSINT P380"), a SiC / Si composite material was manufactured by the selective laser sintering method as follows. First, three-dimensional data of the cross-sectional shape at regular intervals of the target SiC / Si composite material was created in advance. Using a powder deposition modeling machine, a thin layer of the raw material mixture with a thickness of 150 μm was laminated on the bottom surface of the modeling chamber installed in the powder deposition modeling machine. The thin layer was sintered by irradiating a desired area of ​​the thin layer with a 40 W CO2 laser to heat it and form a sintered thin layer (step (a)). Next, the bottom of the molding chamber (the molding table) was lowered by one layer, another thin layer of the raw material mixture was laminated on the sintered thin layer, and a 40 W CO2 laser was scanned and irradiated to the desired area of ​​this thin layer. These lamination and irradiation operations were repeated until the desired SiC / Si composite material was formed, and a rectangular solid-shaped molded body (1) 20 with a length of 10 mm, a width (total length: L1) of 80 mm, and a height of 10 mm was obtained (step (b)) as shown in Figure 1 (a). Next, the raw material mixture in the non-irradiated area of ​​the thin layer was removed to take out the molded body (1). The time required for taking out the molded body (1) was measured. The results are shown in Table 2. The flexural strength and deflection of the molded article (1) were measured. The results are shown in Table 2.

[0055] The removed molded body (1) was placed in a constant temperature incubator (manufactured by Yamato Scientific Co., Ltd., product name "DKN402") and heat-treated at 200°C for 30 minutes, thereby further curing the molding resin composition contained in the molded body (1) to obtain a molded body (2) (step (c)). After the obtained molded body (2) was cooled to room temperature (25° C.), the total length (L2) of the molded body (2) was measured, and the secondary cure shrinkage was calculated. The results are shown in Table 2.

[0056] Next, the molded body (2) was carbonized under reduced pressure in a partial pressure air flow of argon gas (100 Pa) at 1000° C. for 10 hours to obtain a fired body (step (d)). Next, 130 g of the sintered body and 220 g of silicon were held in a vacuum atmosphere of 10 Pa at 1500°C for 3 hours to impregnate the sintered body with silicon and reactively sinter the sintered body, thereby obtaining a SiC / Si composite material (step (e)). The Young's modulus of the obtained SiC / Si composite material was measured, and the results are shown in Table 2.

[0057] [Example 2] A raw material mixture was prepared in the same manner as in Example 1, except that the amount of hexaethylenetetramine added was changed to 3.2 parts by mass, and a SiC / Si composite material was produced using the raw material mixture obtained. The average particle size of the novolac-type phenolic resin (ii) in the molding resin composition was 22 μm. The gel time of the molding resin composition was measured, and the results are shown in Table 1.

[0058] [Example 3] Except for changing the amount of the novolac phenolic resin (ii) to 15 parts by mass and the amount of the hexaethylenetetramine to 1.2 parts by mass, a raw material mixture was prepared in the same manner as in Example 1, and a SiC / Si composite material was produced using the raw material mixture obtained. The average particle size of the novolac phenolic resin (ii) in the molding resin composition was 22 μm. The gel time of the molding resin composition was measured, and the results are shown in Table 1. The reaction rate of the molded body (1) was also measured, and the results are shown in Table 1.

[0059] [Example 4] 15 parts by mass of the novolac phenolic resin (iii) and 2.4 parts by mass of hexaethylenetetramine were pulverized with a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The average particle size of the novolac phenolic resin (iii) in the molding resin composition was 20 μm. The gel time of the obtained molding resin composition was measured, and the results are shown in Table 1. A raw material mixture was prepared in the same manner as in Example 1, except that the obtained molding resin composition was used, and a SiC / Si composite material was produced using the obtained raw material mixture. The molded body (1) was measured for the removal time, bending strength, deflection, and secondary cure shrinkage. The results are shown in Table 2.

[0060] [Example 5] 15 parts by mass of the novolac phenolic resin (iii), 2.4 parts by mass of hexaethylenetetramine, 0.3 parts by mass of benzoic acid, and 0.3 parts by mass of resorcinol were pulverized in a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The average particle size of the novolac phenolic resin (iii) in the molding resin composition was 20 μm. The gel time of the obtained molding resin composition was measured, and the results are shown in Table 1. A raw material mixture was prepared in the same manner as in Example 1, except that the obtained molding resin composition was used, and a SiC / Si composite material was produced using the obtained raw material mixture. The reaction rate, removal time, bending strength, deflection amount, secondary cure shrinkage rate, and Young's modulus of the SiC / Si composite material of the molded body (1) were measured. The results are shown in Tables 1 and 2.

[0061] [Example 6] 15 parts by mass of the novolac phenolic resin (iii), 2.4 parts by mass of hexaethylenetetramine, and 0.3 parts by mass of benzoic acid were pulverized in a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The average particle size of the novolac phenolic resin (iii) in the molding resin composition was 20 μm. The gel time of the obtained molding resin composition was measured, and the results are shown in Table 1. A raw material mixture was prepared in the same manner as in Example 1, except that the obtained molding resin composition was used, and a SiC / Si composite material was produced using the obtained raw material mixture.

[0062] [Example 7] 15 parts by mass of the novolac phenolic resin (iii), 2.4 parts by mass of hexaethylenetetramine, and 0.3 parts by mass of resorcinol were pulverized in a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The average particle size of the novolac phenolic resin (iii) in the molding resin composition was 20 μm. The gel time of the obtained molding resin composition was measured, and the results are shown in Table 1. A raw material mixture was prepared in the same manner as in Example 1, except that the obtained molding resin composition was used, and a SiC / Si composite material was produced using the obtained raw material mixture.

[0063] [Comparative Example 1] 15 parts by mass of the novolac phenolic resin (i) and 1.2 parts by mass of hexaethylenetetramine were pulverized with a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The average particle size of the novolac phenolic resin (i) in the molding resin composition was 20 μm. The gel time of the obtained molding resin composition was measured, and the results are shown in Table 1. A raw material mixture was prepared in the same manner as in Example 1, except that the obtained molding resin composition was used, and a SiC / Si composite material was produced using the obtained raw material mixture. The molded body (1) was measured for the removal time, bending strength, deflection, and secondary cure shrinkage. The results are shown in Table 2.

[0064] [Table 1]

[0065] [Table 2]

[0066] In Table 1, "proportion relative to resin" refers to the amount (parts by mass) of hexaethylenetetramine, benzoic acid or resorcinol added relative to 100 parts by mass of the novolak phenolic resin.

[0067] As is clear from Table 1, when Example 3 and Example 5 are compared, the shorter the gelation time of the molding resin composition, the higher the reaction rate of the molded body (1). The reaction rate of the molded body (1) is an index showing the degree of progress of the primary curing of the molding resin composition, and the higher the reaction rate, the more the primary curing has progressed, that is, the smaller the proportion of uncured molding resin composition in the molded body (1). It was shown that the molding resin composition of Example 5, which has a shorter gelation time than the molding resin composition of Example 3, cures more sufficiently in the primary curing. As is clear from Table 2, in the case of each Example, the removal time of the molded body (1) was shorter and the workability was excellent compared to Comparative Example 1. In addition, in the case of each Example, the amount of deflection was smaller and the secondary cure shrinkage rate was also lower compared to Comparative Example 1. These results demonstrated that the molding resin composition of each Example was sufficiently cured in the primary cure. Furthermore, according to the manufacturing method of this embodiment, a raw material mixture containing 10 parts by mass or more of novolac-type phenolic resin relative to silicon carbide particles is used, and a molded body (1) in which the molding resin composition is primarily cured is molded by three-dimensional additive manufacturing. Therefore, even when manufacturing SiC / Si composite materials with complex shapes, the manufacturing process can be simplified. [Explanation of symbols]

[0068] 10 Pedestal 10a Horizontal surface 20 Molded body (1) 30 Molded body (2)

Claims

1. A step (a) of forming a thin layer of a raw material mixture containing silicon carbide particles and a molding resin composition, irradiating a desired area of ​​the thin layer with a laser, and sintering the thin layer to form a sintered thin layer; A step (b) of performing the step (a) a plurality of times to obtain a molded body (1) in which a plurality of the sintered thin layers are laminated; A step (c) of further curing the molding resin composition contained in the molded body (1) to obtain a molded body (2); A step (d) of carbonizing the organic components contained in the molded body (2) to obtain a fired body; (e) impregnating the sintered body with silicon and reactively sintering the sintered body to obtain a SiC / Si composite material; Including, The method does not include a step of impregnating the molded body (1) with an assist agent containing a carbon source, The molding resin composition contains a novolac phenolic resin and a curing agent, The mass average molecular weight of the novolac phenolic resin is 2,000 to 20,000; the curing agent comprises hexaethylenetetramine; The ratio of the novolac-type phenolic resin to 100 parts by mass of the silicon carbide particles is 10 to 40 parts by mass, The method for producing a SiC / Si composite material, wherein the gel time of the molding resin composition at 150° C. is 120 seconds or less.

2. The method for producing a SiC / Si composite material according to claim 1 , wherein the molding resin composition further contains a curing accelerator.

Citation Information

Patent Citations

  • Lock device for sun window of gardening facility

    JP1982006076A

  • Production of high-molecular-weight novolak

    JP1996301962A

  • Method for manufacturing reaction sintered silicon carbide member

    JP2016204244A

  • Binder coated refractory, casting mold, and method for manufacturing casting mold

    JP2017109206A

  • Method for manufacturing reaction-bonded silicon carbide components

    JP6651754B2